A Novel Carbon Nanotube Field Effect Transistors Based Low-Voltage DC-DC Buck Converter for Maximum Efficiency - Gowri Sankar1, P.A.; Udhayakumar2, K. (Asian Journal of Chemistry, 2013)
This paper presents the design of a novel 32 nm carbon nanotube field effect transistor based low-voltage DC-DC Buck converter. It mainly aims to improve the buck converter efficiency and frequency range of its operation against the low-dropout regulator. Aside from efficiency and operating frequency, the proposed buck converter also meets specifications for low output ripple voltage, fast settling at start up and after steps in input voltage or load current. These circuits are simulated in HSPICE with the electrical parameters of standard 32 nm carbon nanotube field effect transistors (CNFETs) technology. The proposed DC-DC buck converter efficiency is calculated by analyzing the amount of conduction and switching losses occur at various load and switching frequency conditions. The simulation results show that the converter is well regulated in the output voltage range for a wide range of switching frequency with maximum efficiency.